Implementation of water treatment processes to optimize the water saving in chemically enhanced oil recovery and hydraulic fracturing methods. (November 2021) - Zhang, Chenguang; Long, Xiting; Tang, Xiangwei; Lekomtsev, Aleksandr; Korobov, Grigory Yurievich
Abstract: Water scarcity is one of the main challenges worldwide that might propose various engineering and economic issues. Petroleum industries have encountered these issues seriously, which required pretreatment facilities before reinjecting the produced water into the production wells. To assure that the treated water has no side effect on the environment, the treatment processes would perform three times by the photo-Fenton flotation method. This paper, it is aimed to calculate the treated water, required water, and saving water for chemically enhanced oil recovery methods (CEOR), hydraulic fracturing (HF), and other service facilities for completion and drilling performances. According to the results of this study, oil-well#3 has the highest water savings among all the wells with the 89% of daily water-saving, and oil-well#4 has the highest water savings among oil wells with the 75% of daily water saving. Consequently, in Sirri oilfield, the water-saving percentage is about 82% and 72%, which indicated that it is required 18%, 28% of the total water volume for implantation of HF process and CEOR methods, respectively. The total annual required water for this oilfield is 4131 MM m 3 /Day.